Thermosetting resin and use thereof
The development of a thermosetting resin with a benzoxazine ring structure addresses the insufficient thermal properties of benzoxazine compounds, achieving enhanced heat resistance and stability through a high carbon content at elevated temperatures.
Patent Information
- Application Number
- JP2023181346
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-05-02
AI Technical Summary
The thermal properties of benzoxazine compounds, particularly heat resistance and thermal stability, are insufficient, limiting their performance in hardened molded bodies.
A thermosetting resin with a benzoxazine ring structure in its main chain, represented by a specific general formula, is developed. This resin has a carbon content of 85% by weight or more, as measured by X-ray photoelectron spectroscopy after reaching 1000°C, indicating enhanced thermal stability.
The thermosetting resin achieves excellent thermal properties in hardened molded bodies, with improved heat resistance and thermal stability, as evidenced by high carbon content retention at elevated temperatures.
Smart Images

Figure 2025070796000019 
Figure 2025070796000020 
Figure 2025070796000021
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermosetting resin and its use. [Background technology]
[0002] It is known that benzoxazine compounds are cured by ring-opening polymerization and reaction of benzoxazine rings due to heat or the like. For example, Patent Document 1 discloses a curable resin composition containing a benzoxazine compound, and a film and a prepreg using the same. Patent Document 2 describes a method of impregnating a thermosetting resin composition containing a benzoxazine compound into a reinforcing fiber substrate to obtain a prepreg, and then graphitizing the prepreg. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-148562 A [Patent Document 2] JP 2018-62540 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, it has been pointed out that the thermal properties of benzoxazine compounds, particularly heat resistance and thermal stability, are insufficient. Therefore, the thermal properties of the conventional benzoxazine compounds described above have room for improvement after curing. One aspect of the present invention aims to realize a thermosetting resin that can provide a cured molded product with excellent thermal properties. [Means for solving the problem]
[0005] In order to solve the above problems, a thermosetting resin according to one embodiment of the present invention is a thermosetting resin having a benzoxazine ring structure in the main chain, as represented by general formula (I), wherein the carbon content of the resin or a cured product of the resin, when it reaches a maximum temperature of 1000°C at a heating rate of 5°C / min under a nitrogen flow of 0.5 mL / min, is measured by X-ray photoelectron spectroscopy and is 85% by weight or more, where the sum of the carbon, nitrogen, and oxygen contents is 100% by weight.
[0006] [ka]
[0007] [In the general formula (I), Ar 1 and Ar 2 represents a trivalent aromatic group derived from a phenolic compound (A) other than vanillin, Ar 1 and Ar 2 may be the same or different, R 1 represents a divalent aromatic group derived from the aromatic diamine compound (B) and represented by any one or more of general formulas (II) to (V).
[0008] [ka]
[0009] [In the general formula (II), The asterisk indicates a bond. The positional relationship of the main chain bonds, excluding R, which are bonded to the aromatic ring is meta or para; R is a substituent on the aromatic ring and represents an aliphatic group having 1 to 10 carbon atoms, the number of R is 0 or 1 or more, and when the number of R is 2 or more, they may be the same or different, m1 and m2 each represent 0 or 1.
[0010] [ka]
[0011] [In the general formula (III), The asterisk indicates a bond. The positions of the main chain bonds, excluding R, that are bonded to the two aromatic rings are meta or para, L1 represents one or more of a single bond, an isopropylidene group, a sulfonyl group, a carbonyl group, a 9,9-fluorenyl group, an oxy group, and an alkylene group; R is a substituent on an aromatic ring and represents an aliphatic group having 1 to 10 carbon atoms, the number of R in each aromatic ring is 0 or 1 or more, and when the number of R is 2 or more, they may be the same or different; m3 and m4 each represent 0 or 1.
[0012] [ka]
[0013] [In the general formula (IV), The asterisk indicates a bond. The positions of the main chain bonds, excluding R, that are bonded to the three aromatic rings are meta or para, L2 and L3 each represent an oxy group. R is a substituent on an aromatic ring and represents an aliphatic group having 1 to 10 carbon atoms, the number of R in each aromatic ring is 0 or 1 or more, and when the number of R is 2 or more, they may be the same or different; m5 and m6 each represent 0 or 1.
[0014] [ka]
[0015] [In the general formula (V), The asterisk indicates a bond. The positions of the main chain bonds, excluding R, that are bonded to the four aromatic rings are meta or para, L4 and L6 each represent an oxy group. L5 represents one or more of a single bond, an isopropylidene group, a sulfonyl group, a carbonyl group, and a 9,9-fluorenyl group; R is a substituent on an aromatic ring and represents an aliphatic group having 1 to 10 carbon atoms, the number of R in each aromatic ring is 0 or 1 or more, and when the number of R is 2 or more, they may be the same or different; m7 and m8 each represent 0 or 1. Effect of the Invention
[0016] According to one aspect of the present invention, it is possible to provide a thermosetting resin that can provide a cured molded product with excellent thermal properties. [Brief description of the drawings]
[0017] [Figure 1] 1 is a GPC chart of an aldehyde group-containing benzoxazine compound (a) of Production Example 1. [Diagram 2] 1 is a GPC chart of an aldehyde group-containing benzoxazine compound (b) of Production Example 2. [Diagram 3] FIG. 2 is a diagram showing the storage modulus of Example 1, Example 2, and Comparative Example 1. [Figure 4] FIG. 2 is a diagram showing the remaining weight ratios of Example 1, Example 2, and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] An embodiment of the present invention will be described below. Unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more (including A and larger than A) and B or less (including B and smaller than B)."
[0019] [1. Thermosetting resin] A thermosetting resin according to one embodiment of the present invention has a benzoxazine ring structure represented by general formula (I) in the main chain.
[0020] [ka]
[0021] In formula (I), Ar 1 and Ar 2 represents a trivalent aromatic group derived from the phenol compound (A) other than vanillin. In this specification, the aromatic group refers to an organic group having at least one aromatic ring. Ar 1 and Ar 2 and may be the same or different. The phenol compound (A) may be one type or two or more types.
[0022] R 1 represents a divalent aromatic group represented by any one or more of general formulas (II) to (V) described later, which is derived from the aromatic diamine compound (B). The aromatic diamine compound (B) may be one type or two or more types.
[0023] R 1 represents a divalent aromatic group represented by any one or more of general formulas (II) to (V) described later, which is derived from the aromatic diamine compound (B). The aromatic diamine compound (B) may be one type or two or more types.
[0024] The thermosetting resin has an aldehyde group as represented by the general formula (I), which contributes to improving the thermal properties of a cured molded article obtained by curing the thermosetting resin.
[0025] The phenol compound (A) is preferably a phenol compound having an aldehyde group. The phenol compound (A) having an aldehyde group does not include vanillin. Examples of the phenol compound having an aldehyde group include 4-hydroxybenzaldehyde and 2-hydroxybenzaldehyde. Among them, 4-hydroxybenzaldehyde is preferred from the viewpoint of easy synthesis of the thermosetting resin.
[0026] R 1 is represented by any one or more of the following general formulas (II) to (V) derived from an aromatic diamine compound (B).
[0027] [ka]
[0028] In general formula (II), an asterisk indicates a bond. The positional relationship of the main chain bond excluding R, which is bonded to the aromatic ring, is meta or para. R is a substituent on the aromatic ring and indicates an aliphatic group having 1 to 10 carbon atoms. The number of R is 0 or 1 or more. When the number of R is 2 or more, they may be the same or different. m1 and m2 each indicate 0 or 1.
[0029] [ka]
[0030] In general formula (III), an asterisk indicates a bond. The positional relationship of the main chain bonds excluding R, which are bonded to the two aromatic rings, is meta or para. L1 indicates one or more of a single bond, an isopropylidene group, a sulfonyl group, a carbonyl group, a 9,9-fluorenyl group, an oxy group, and an alkylene group. R is a substituent on the aromatic ring and indicates an aliphatic group having 1 to 10 carbon atoms. The number of R in each aromatic ring is 0 or 1 or more. When the number of R is 2 or more, they may be the same or different. m3 and m4 each indicate 0 or 1.
[0031] [ka]
[0032] In general formula (IV), an asterisk indicates a bond. The positional relationship of the main chain bonds excluding R, which are bonded to the three aromatic rings, is meta or para. L2 and L3 each indicate an oxy group. R is a substituent on the aromatic ring and indicates an aliphatic group having 1 to 10 carbon atoms. The number of R in each aromatic ring is 0 or 1 or more. When the number of R is 2 or more, they may be the same or different. m5 and m6 each indicate 0 or 1.
[0033] [ka]
[0034] In the general formula (V), an asterisk indicates a bond. The positional relationship of the main chain bonds excluding R, which are bonded to the four aromatic rings, is meta or para. L4 and L6 each indicate an oxy group. L5 indicates one or more of a single bond, an isopropylidene group, a sulfonyl group, a carbonyl group, and a 9,9-fluorenyl group. R is a substituent on the aromatic ring and indicates an aliphatic group having 1 to 10 carbon atoms. The number of R in each aromatic ring is 0 or 1 or more. When the number of R is 2 or more, they may be the same or different. m7 and m8 each indicate 0 or 1.
[0035] In other words, the aromatic diamine compound (B) is represented by any one of the following general formulas (IIa) to (Va): In general formulas (IIa) to (Va), the definitions of L1 to 6, R, and m1 to 8 are the same as those in general formulas (II) to (V).
[0036] [ka]
[0037] From the viewpoint of availability and ease of synthesis of the thermosetting resin, the aromatic diamine compound (B) is preferably 4,4'-oxydianiline, 3,3'-methylenedianiline, 4,4'-methylenedianiline, 4,4'-diaminodiphenyl ether, 1,4-diaminobenzene, 1,3-diaminobenzene, 2,4-diaminotoluene, 2,6-diaminotoluene, 3-(aminomethyl)benzylamine, 4-(aminomethyl)benzylamine, 3,3'-sulfonyldianiline, 4,4'-sulfonyldianiline, 3,3'- It is preferable that the compound is at least one selected from the group consisting of diaminobenzophenone, 4,4'-diaminobenzophenone, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, bis[4-(4-aminophenoxy)phenyl]sulfone, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, and 9,9-bis(4-aminophenyl)fluorene.
[0038] Among the above-mentioned group, the aromatic diamine compound (B) is more preferably at least one selected from the group consisting of 4,4'-oxydianiline, 4,4'-diaminodiphenyl ether, 1,4-diaminobenzene, 1,3-diaminobenzene, 2,4-diaminotoluene, 2,6-diaminotoluene, 3-(aminomethyl)benzylamine, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, bis[4-(4-aminophenoxy)phenyl]sulfone, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, and 9,9-bis(4-aminophenyl)fluorene. 3-(Aminomethyl)benzylamine is also called m-xylene-α,α'-diamine.
[0039] The thermosetting resin may or may not contain a structure other than the benzoxazine ring structure represented by formula (I). The thermosetting resin may also contain a structure derived from an aliphatic monoamine or a (poly)oxyalkylene monoamine compound.
[0040] In the thermosetting resin or the cured product of the resin according to one embodiment of the present invention, the lower limit of the carbon content measured by X-ray photoelectron spectroscopy at the time of reaching the maximum temperature of 1000°C under a nitrogen flow of 0.5 mL / min at a heating rate of 5°C / min is 85% by weight or more, preferably 90% by weight or more, and more preferably 94% by weight or more, where the total content of carbon, nitrogen, and oxygen is 100% by weight. The upper limit of the carbon content is not particularly limited, and may be, for example, 97% by weight or less. If the carbon content is in the above range, it is preferable from the viewpoint of preventing the generation of decomposition gas and / or change in shape during practical use at high temperatures.
[0041] The residual weight ratio of the thermosetting resin according to one embodiment of the present invention, when measured by thermogravimetry (TGA) at a temperature rise rate of 5°C / min under a nitrogen gas flow of 200 mL / min at a maximum temperature of 1000°C, is preferably 65% or more, more preferably 68% or more, and even more preferably 70% or more. The upper limit of the residual weight ratio is not particularly limited, and the higher the residual weight ratio, the better. If the residual weight ratio is within the above range, the stiffness, strength, heat insulation, etc. of the obtained cured product and carbon material are excellent.
[0042] In addition, the residual weight ratio of the thermosetting resin according to one embodiment of the present invention is preferably 65% or more, more preferably 68% or more, and even more preferably 70% or more, when measured by measuring the actual weight at the time when the maximum temperature of 1000°C is reached at a temperature increase rate of 5°C / min under a nitrogen flow of 0.5 mL / min. The upper limit of the residual weight ratio is not particularly limited, and the higher the residual weight ratio, the better. If the residual weight ratio is within the above range, the stiffness, strength, heat insulation, etc. of the obtained cured product and carbon material are excellent. In this specification, the residual weight ratio is also called "weight retention ratio".
[0043] Although not particularly limited, the method for producing a thermosetting resin according to one embodiment of the present invention includes, for example, a step (s1) of reacting a phenol compound (A), an aromatic diamine compound (B), and an aldehyde compound (C), in which the phenol compound (A) has an aldehyde group, and the aromatic diamine compound (B) is represented by any one or more of general formulas (IIa) to (Va).
[0044] The above-mentioned thermosetting resin can be produced by the production method. The benzoxazine ring can be formed by step (s1).
[0045] The above-mentioned compounds can be used as the phenol compound (A) and the aromatic diamine compound (B). The aldehyde compound (C) is not particularly limited, but formaldehyde is preferred. As the formaldehyde, paraformaldehyde, which is a polymer, or formalin, which is in the form of an aqueous solution, can be used.
[0046] The molar ratio of the phenol compound (A) to the aromatic diamine compound (B) in step (s1) is preferably about 2:1, but may be 2.5 / 1 to 1.95 / 1. The molar ratio of the phenol compound (A) to the aldehyde compound (C) in step (s1) is preferably 1 / 1 to 1 / 20, more preferably 1 / 2 to 1 / 6. When the molar ratio of the bifunctional phenol compound (A) to the aldehyde compound (C) is within the above range, a benzoxazine ring can be suitably produced.
[0047] The reaction in step (s1) may be carried out in a solvent. Examples of the solvent include halogenated solvents such as chloroform, non-halogenated aromatic hydrocarbon solvents such as toluene and xylene, ether solvents such as tetrahydrofuran (THF), cyclic diether solvents such as 1,4-dioxane and 1,3-dioxolane, highly polar and high boiling point solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N,N-diethylacetamide, N-methylcaprolactam, γ-butyrolactone, and dimethylsulfoxide, and mixed solvents of non-halogenated hydrocarbon solvents and aliphatic alcohol solvents. Examples of aliphatic alcohol solvents include methanol, ethanol, propanol, and butanol (including structural isomers). From the viewpoint of suppressing side reactions, it is preferable to use a non-halogenated aromatic hydrocarbon solvent in step (s1).
[0048] The reaction temperature in step (s1) is preferably 25 to 150° C., more preferably 40 to 120° C. The reaction time in step (s1) is preferably 0.5 to 24 hours, more preferably 1 to 20 hours.
[0049] In order to obtain the reaction intermediate as a precipitate in step (s1), the reaction solution may be added to a non-halogenated aliphatic hydrocarbon solvent such as hexane, etc. Also, in step (s1), the product may be washed with an aliphatic alcohol solvent.
[0050] [2. Composition] An embodiment of the present invention also includes a composition containing the above-mentioned thermosetting resin. The composition contains the thermosetting resin as a main component, and may contain other thermosetting resins, thermoplastic resins, and compounding agents as subcomponents.
[0051] Examples of other thermosetting resins include epoxy resins, thermosetting modified polyphenylene ether resins, thermosetting polyimide resins, silicon resins, melamine resins, urea resins, allyl resins, phenol resins, unsaturated polyester resins, bismaleimide resins, alkyd resins, furan resins, polyurethane resins, and aniline resins.
[0052] Examples of the thermoplastic resin include a thermoplastic epoxy resin and a thermoplastic polyimide resin.
[0053] Examples of compounding agents include flame retardants, nucleating agents, antioxidants, antiaging agents, heat stabilizers, light stabilizers, ultraviolet absorbers, lubricants, flame retardant assistants, antistatic agents, antifogging agents, fillers, softeners, plasticizers, colorants, etc., as required. These may be used alone or in combination of two or more. Reactive or non-reactive solvents may also be used.
[0054] 3. Uncured Molded Body and Cured Molded Body An embodiment of the present invention also includes an uncured molded article obtained by molding the above-mentioned thermosetting resin or composition. Also, an embodiment of the present invention also includes a cured molded article obtained by curing the above-mentioned thermosetting resin, composition, or uncured molded article.
[0055] In this specification, the term "uncured molded body" refers to a molded body having a degree of cure of less than 1%, and the term "cured molded body" refers to a molded body having a degree of cure of 1 to 100%. In other words, the term "cured molded body" also includes molded bodies that are only partially cured. As shown in the examples below, the degree of cure can be calculated from the ratio of the areas of the exothermic peaks obtained from the DSC curves of the uncured resin and the uncured or cured molded body.
[0056] The dimensions and shapes of the uncured molded body and the cured molded body are not particularly limited, and examples thereof include a film, a sheet, a plate, a block, etc. The uncured molded body and the cured molded body may have other layers (e.g., an adhesive layer) in addition to the layer made of the above-mentioned thermosetting resin or composition.
[0057] From the viewpoint of mechanical properties, the glass transition temperature (Tg) of the uncured molded product is preferably 300° C. or lower, more preferably 250° C. or lower, and even more preferably 200° C. or lower. From the viewpoint of heat resistance, the glass transition temperature of the uncured molded product is preferably 30° C. or higher, more preferably 40° C. or higher, and even more preferably 50° C. or higher.
[0058] From the viewpoint of heat resistance, the glass transition temperature of the cured molded product is preferably 150° C. or higher, more preferably 190° C. or higher, even more preferably 200° C. or higher, and most preferably 220° C. or higher. There is no particular upper limit to the glass transition temperature of the cured molded product, but it may be, for example, 400° C. or lower.
[0059] The thermal stability of the uncured molded body and the cured molded body can be evaluated, for example, by the 5% weight loss temperature (Td5) in thermogravimetry (TGA) measurement, or the residual weight rate at 500°C, 800°C, or 1000°C. The 5% weight loss temperature of the uncured molded body is preferably 100°C or higher, more preferably 150°C or higher, and even more preferably 200°C or higher. The 5% weight loss temperature of the cured molded body is preferably 250°C or higher, more preferably 300°C or higher, even more preferably 320°C or higher, and most preferably 340°C or higher.
[0060] The residual weight percentage of the cured molded product at 500° C. is preferably 60% or more, more preferably 70% or more, and even more preferably 75% or more. The residual weight percentage of the cured molded product at 800° C. and 1000° C. is preferably 55% or more, more preferably 60% or more, and even more preferably 65% or more.
[0061] From the viewpoint of mechanical properties, the tensile modulus of the uncured molded body and the cured molded body is preferably 10 GPa or less, more preferably 8 GPa or less, and even more preferably 5 GPa or less. From the viewpoint of ease of handling, the tensile modulus of the uncured molded body and the cured molded body is preferably 0.1 GPa or more, more preferably 0.5 GPa or more, and even more preferably 1 GPa or more.
[0062] From the viewpoint of resistance to breakage, the tensile breaking strength of the uncured molded body and the cured molded body is preferably 5 MPa or more, more preferably 10 MPa or more, and even more preferably 50 MPa or more.
[0063] From the viewpoint of mechanical properties, the tensile elongation at break of the uncured molded body and the cured molded body is preferably 1% or more, more preferably 2% or more, and even more preferably 3% or more.
[0064] The weight retention rate measured by actual weight measurement at room temperature after the uncured molded body and the cured molded body are fired to 1000°C at a heating rate of 5°C / min under a nitrogen flow of 0.5mL / min is preferably 60% or more, more preferably 65% or more, and even more preferably 70% or more. The upper limit of the weight retention rate after firing the uncured molded body and the cured molded body is not particularly limited, and the higher the value, the better. If the weight retention rate is 60% or more, the uncured molded body and the cured molded body after firing to 1000°C under the above conditions can exhibit excellent strength. Here, the uncured molded body and the cured molded body after firing to 1000°C under the above conditions can also be called a carbon material.
[0065] The dimensional retention rate in the in-plane direction after firing of the uncured molded body and the cured molded body is preferably 70% or more, more preferably 75% or more, and even more preferably 80% or more. The upper limit of the dimensional retention rate in the in-plane direction after firing of the uncured molded body and the cured molded body is not particularly limited, and the higher the value, the better. If the dimensional retention rate in the in-plane direction is 70% or more, for example, the dimensional change of the structure is small, and high mechanical strength can be exhibited.
[0066] The thickness dimension retention rate of the uncured molded body and the cured molded body after firing is preferably 70% or more, more preferably 75% or more, and even more preferably 80% or more. The upper limit of the thickness dimension retention rate of the uncured molded body and the cured molded body after firing is not particularly limited, and the higher the value, the better. If the thickness dimension retention rate is 70% or more, for example, the dimensional change of the structure is small, and high mechanical strength can be exhibited.
[0067] The method for forming the uncured molded body and the cured molded body is not particularly limited, and examples thereof include a method in which the above-mentioned thermosetting resin or composition is dissolved in a solvent and the resulting solution is cast onto a substrate to form the molded body (casting method), and a method in which the above-mentioned thermosetting resin or composition is pressed to form the molded body (pressing method). Examples of the solvent used in the casting method include N,N-dimethylformamide (DMF), tetrahydrofuran (THF), chloroform, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N,N-diethylacetamide, N-methylcaprolactam, γ-butyrolactone, cyclohexanone, dimethylsulfoxide, cyclopentanone, 1,4-dioxane, and 1,3-dioxolane. The pressure in the pressing method is not particularly limited, and may be, for example, 0.1 to 5.0 MPa.
[0068] The molding temperature of the uncured molded product (the maximum temperature when the temperature is gradually increased) is not particularly limited, but is preferably room temperature or higher and less than 200°C, more preferably 40 to 180°C, and even more preferably 60 to 160°C. The curing temperature of the cured molded product (the maximum temperature when the temperature is gradually increased) is not particularly limited, but is preferably 200 to 300°C, more preferably 210 to 280°C, and even more preferably 220 to 260°C.
[0069] The uncured molded article can be used as a precursor of the cured molded article, and can also be used, for example, as a curable adhesive sheet. The cured molded article can be suitably used for electronic parts and electronic devices, and materials thereof, particularly for multilayer boards, laminates, sealants, adhesives, etc., which require excellent dielectric properties, and can also be used for aircraft parts, automobile parts, building parts, etc.
[0070] The cured molded product may contain reinforcing fibers from the viewpoint of improving the mechanical strength of the cured molded product. Examples of reinforcing fibers include inorganic fibers, organic fibers, metal fibers, and hybrid reinforcing fibers that combine these fibers. The reinforcing fibers may be one type or two or more types.
[0071] Examples of inorganic fibers include carbon fibers, graphite fibers, silicon carbide fibers, alumina fibers, tungsten carbide fibers, boron fibers, and glass fibers. Examples of organic fibers include aramid fibers, high-density polyethylene fibers, and other general nylon fibers and polyester fibers. Examples of metal fibers include fibers of stainless steel and iron. Examples of metal fibers include carbon-coated metal fibers in which metal fibers are coated with carbon. Among these, from the viewpoint of increasing the strength of the cured molded body, it is preferable that the reinforcing fibers are carbon fibers.
[0072] Generally, the carbon fibers are subjected to a sizing treatment, but they may be used as they are, or, if necessary, fibers using a small amount of sizing agent may be used, or the sizing agent may be removed by an existing method such as an organic solvent treatment or a heat treatment. Also, the carbon fiber bundles may be opened in advance using air or a roller, and a treatment may be performed to make it easier to impregnate the spaces between the carbon fiber single yarns with a resin.
[0073] The cured molded product can be used as a carbon fiber composite material. Carbon fiber composite materials are also called carbon fiber reinforced plastics (CFRP). The method for producing the carbon fiber composite material is not particularly limited, but for example, a method using semipreg or prepreg, which is a sheet of carbon fiber impregnated with resin, or a method of impregnating carbon fiber (bundle-like or woven) with liquid resin may be used. The cured molded product may be molded into a semipreg or prepreg described in the following section [4. Semipreg and Prepreg], and the semipreg or prepreg may be used to produce the carbon fiber composite material.
[0074] The carbon fiber is not particularly limited as long as it is a material having a carbon content in the range of 85 to 100% by weight and a continuous fiber shape having at least a partial graphite structure. Specific examples include polyacrylonitrile (PAN)-based, rayon-based, lignin-based, and pitch-based carbon fibers. Among these, PAN-based or pitch-based carbon fibers are preferred because they are versatile, inexpensive, and have high strength.
[0075] In one embodiment of the present invention, the weight content of carbon fiber contained in CFRP is preferably 20 to 95% by weight, more preferably 40 to 90% by weight, and further preferably 50 to 85% by weight. If the carbon fiber content is low, it becomes difficult to obtain high mechanical strength when made into a carbon fiber composite material, and if the resin content is too low, the rigidity of carbon fiber may not be obtained.
[0076] Although a carbon fiber composite material is given as an example here, as described above, the reinforcing fibers that can be used are not limited to carbon fibers. That is, one embodiment of the present invention also includes a fiber composite material (also called a reinforced fiber composite material) obtained by impregnating a reinforcing fiber with the above-mentioned thermosetting resin or composition and then curing it.
[0077] [4. Semipreg and prepreg] One embodiment of the present invention also includes a prepreg or semipreg obtained by impregnating reinforcing fibers with the above-mentioned thermosetting resin or composition. In this specification, the term "semipreg" refers to a composite in which the reinforcing fibers are partially impregnated (semi-impregnated) with the thermosetting resin or composition and integrated. In addition, a prepreg can be obtained from the semipreg. For example, the semipreg can be further heated and melted to impregnate the reinforcing fibers with the resin, thereby obtaining a prepreg. In other words, in this specification, the prepreg can be said to be a reinforcing fiber in which the degree of resin impregnation is more advanced than that of a semipreg.
[0078] The semipreg or prepreg may be obtained, for example, by placing the cured molded body on both sides of a sheet (plain weave reinforcing fiber material) in which the reinforcing fibers have been previously impregnated with resin, and pressing them at a predetermined temperature and pressure.
[0079] The prepreg or semipreg according to one embodiment of the present invention may be present in a state in which a plurality of prepregs are laminated together. A laminate of a plurality of prepregs is also called a prepreg laminate, and a laminate of a plurality of semipregs is also called a semipreg laminate.
[0080] Furthermore, the prepreg or semipreg according to one embodiment of the present invention preferably has adhesiveness to other substrates (metals) etc. By having the adhesiveness, the prepreg or semipreg can be adhered to other substrates without the need for an adhesive.
[0081] The fiber composite material described in the above section [3. Uncured molded body and cured molded body] may be a fiber composite material obtained by using only the semipreg or prepreg according to one embodiment of the present invention, or may be a fiber composite material obtained by laminating together the semipreg or prepreg according to one embodiment of the present invention and a prepreg or semipreg obtained by impregnating a reinforcing fiber with another resin or a composition thereof. The other resin is not particularly limited, and may be, for example, another thermosetting resin or thermoplastic resin listed in [2. Composition]. The composition may contain the other resin as a main component, and may further contain, for example, another thermosetting resin (excluding the other resin), thermoplastic resin (excluding the other resin), and compounding agent listed in [2. Composition]. That is, one embodiment of the present invention also includes a fiber composite material obtained by impregnating a reinforcing fiber with the above-mentioned thermosetting resin or composition and then curing it, and a fiber composite material obtained by impregnating a reinforcing fiber with another resin or a composition thereof and curing the thermosetting resin or the composition, which are integrated to an inseparable extent.
[0082] The form of the fiber material constituting the prepreg or fiber composite material may be a continuous fiber-shaped structure formed by bundle (UD, uni-directional), weaving (plain weave, satin weave, etc.), knitting, etc. The structure is not particularly limited and may be appropriately selected depending on the purpose, and these may be used alone or in combination.
[0083] The molding method of the fiber composite material is not particularly limited, and may include a step of impregnating the reinforcing fiber with the thermosetting resin or composition to obtain a prepreg or semipreg, and a step of curing the prepreg or semipreg to obtain a fiber composite material. The molding method may further include a step of pre-curing the prepreg or semipreg obtained in the step of obtaining the prepreg or semipreg after the step of obtaining the prepreg or semipreg to obtain a pre-cured prepreg having a degree of curing of more than 0% to 99%. When the step of obtaining the pre-cured prepreg is included, the target of curing in the step of obtaining the fiber composite material is the pre-cured prepreg. Here, in this specification, pre-curing means partially curing the prepreg or semipreg. In addition, the molding method may further include a step of deforming the prepreg or semipreg before pre-curing the prepreg or semipreg.
[0084] [5. Carbon Materials] One embodiment of the present invention also includes a carbon material obtained by carbonizing and / or graphitizing the uncured or cured molded body described above. Another embodiment of the present invention also includes a carbon material obtained by further carbonizing and / or graphitizing a fiber composite material obtained by impregnating a reinforcing fiber with the above-mentioned composition and then curing the fiber composite material. Still another aspect of the present invention also includes a carbon material obtained by carbonizing and / or graphitizing the above-mentioned prepreg or semipreg.
[0085] In the production of the carbon material, carbonization (also referred to as "calcination" in this specification) generally refers to a step of performing a heat treatment at a temperature of about 1000° C. For example, when preheating is performed from room temperature at a temperature increase rate of 5° C. / min under a nitrogen gas flow of 0.5 mL / min, the heat treatment is preferably a heat treatment in which temperature treatment is performed for about 30 minutes in a temperature range of about 1000° C.
[0086] In the production of the carbon material, the graphitization can be carried out under reduced pressure or in an inert gas. As the inert gas, argon is preferably used, and it is more preferable to use argon in combination with a small amount of helium. The graphitization can be carried out at a heat treatment temperature of 2400°C or higher, and the heat treatment temperature is more preferably 2600°C or higher, further preferably 2800°C or higher, and particularly preferably 2900°C or higher. When both carbonization and graphitization are carried out, the graphitization may be carried out continuously following the carbonization, or the temperature may be cooled once after the carbonization and then the graphitization may be carried out alone.
[0087] The elemental components contained in the carbon material according to one embodiment of the present invention can be measured by X-ray photoelectron spectroscopy. In the measurement, the contents of carbon, oxygen, and nitrogen can be measured. When the total of the contents (g) of carbon, oxygen, and nitrogen is taken as 100% by weight, the carbon content of the carbon material is preferably 85% by weight or more, more preferably 90% by weight or more, and more preferably 94% by weight or more, from the viewpoint of preventing the generation of decomposition gas and / or shape change during practical use at high temperatures. The upper limit of the carbon content is not particularly limited, but may be, for example, 97% by weight or less. In the present specification, the carbon content of the carbon material is also simply referred to as the "carbon content". In addition, if the carbon content is within the above range, it means that carbonization has been sufficiently performed.
[0088] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention.
[0089] [6. Summary] An embodiment of the present invention may have the following configuration. <1> A thermosetting resin having a benzoxazine ring structure in its main chain, represented by general formula (I): The resin or a cured product of the resin has a carbon content of 85% by weight or more when measured by X-ray photoelectron spectroscopy at a maximum temperature of 1000°C under a nitrogen gas flow of 0.5 mL / min at a heating rate of 5°C / min., where the total of the carbon, nitrogen, and oxygen contents is 100% by weight. Thermosetting resin. <2> the aromatic diamine compound (B) is at least one selected from the group consisting of 4,4'-oxydianiline, 1,4-diaminobenzene, 1,3-diaminobenzene, 2,4-diaminotoluene, 2,6-diaminotoluene, 3-(aminomethyl)benzylamine, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, bis[4-(4-aminophenoxy)phenyl]sulfone, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, and 9,9-bis(4-aminophenyl)fluorene; <1> The thermosetting resin according to claim 1. <3> <1> or <2> A composition comprising the thermosetting resin according to claim 1. <4> <3> An uncured molded article obtained by molding the composition according to claim 1. <5> <3> 2. A cured molded article obtained by curing the composition according to claim 1. <6> <3> A prepreg or semipreg obtained by impregnating reinforcing fibers with the composition described in claim 1. <7> <4> or the uncured molded article according to <5> A carbon material obtained by carbonizing and / or graphitizing the cured molded body according to claim 1. <8> <3> 2. A carbon material obtained by impregnating reinforcing fibers with the composition described in claim 1, followed by curing the resulting fiber composite material, and then carbonizing and / or graphitizing the resulting fiber composite material. <9> <6> A carbon material obtained by carbonizing and / or graphitizing the prepreg or semipreg described in claim 1. EXAMPLES
[0090] An embodiment of the present invention will be described below. In the following, the benzoxazine compound corresponds to a thermosetting resin, the cured film corresponds to a cured molded product, and the uncured film corresponds to an uncured molded product.
[0091] [Test Method] <Structural analysis of benzoxazine compounds> The molecular structure of the benzoxazine compound was analyzed. Specifically, a nuclear magnetic resonance spectrometer (NMR, Bruker, AVANCEIII 400MHz) was used, and the number of accumulations was 16, and the measurement temperature was room temperature. 1 H-NMR measurements were performed.
[0092] <Measurement of molecular weight of benzoxazine compounds> The molecular weight of the benzoxazine compound was measured using a gel permeation chromatograph (GPC) (Shimadzu Corporation, Prominence UFLC). In the measurement, DMF containing 0.01 mol / L lithium chloride was used as the eluent, three TSKgel GMHHR-M columns were connected in series, the flow rate was 1 mL / min, the injection amount was 20 μL, the column temperature was 40° C., a UV detector was used for detection, and polystyrene was used as a sample for the calibration curve.
[0093] <Measurement of the degree of curing of cured film> The degree of cure of the cured film was determined as follows. First, a differential scanning calorimeter (DSC, Hitachi High-Tech Science, DSC7000X) was used to measure the DSC curve under conditions of a nitrogen flow rate of 40 mL / min and 5°C / min. Next, the degree of cure was calculated from the amount of heat generated by the curing due to the ring opening of benzoxazine according to the following formula. Degree of cure [%] = 100 - {(amount of heat generated after cure) / (amount of heat generated before cure) x 100} Here, the amount of heat generated before curing represents the area of the exothermic peak in the DSC curve of the uncured resin, and the amount of heat generated after curing represents the area of the exothermic peak in the DSC curve of the cured film.
[0094] <Glass transition temperature (Tg) and storage modulus of uncured and cured films> The Tg and storage modulus of the uncured and cured films were measured using a dynamic viscoelasticity measuring device (DMA, TA Instruments, RSA G2, tensile mode) at a frequency of 1 Hz and a heating rate of 5° C. / min. The extrapolated glass transition onset temperature (the intersection of the straight line extrapolated to the high temperature side from the baseline before the inflection point and the tangent to the inflection point) obtained from the resulting DMA curve was taken as the Tg in this example.
[0095] <Chemical heat resistance of uncured and cured films> The chemical heat resistance of the uncured and cured films was evaluated in terms of the 5% weight loss temperature (Td5) and the residual weight (wt%) at 500°C, 800°C, and 1000°C. Td5 and the residual weight at 500°C, 800°C, and 1000°C were measured by thermogravimetry (TGA) measurement using a thermogravimetric analyzer (STA7200, Hitachi High-Tech Science Corporation) at a heating rate of 5°C / min under a nitrogen gas flow of 200mL / min. The residual weight was calculated from the following formula: Residual weight rate [%] = (weight (g) after heating at each temperature) / (weight (g) before TGA measurement) × 100 <Mechanical properties of uncured and cured films> A tensile test was carried out on the uncured and cured films using a tensile tester (Shimadzu Corporation, EZ-SX). The test temperature was room temperature, the tensile speed was 5 mm / min, and the test piece shape was 40 mm long and 3 mm wide. The tensile modulus, tensile strength, and elongation-at-break were measured.
[0096] <Weight retention of cured film after baking> The weight retention of the cured film after baking was measured by actual weight measurement. The weight of a 5 cm square cured film was measured before and after baking, and the weight retention of the cured film after baking was calculated using the following calculation method. Weight retention rate (%) = weight after firing (g) x 100 / weight before firing (g) <Dimensional retention of cured film after baking> A 5 cm square cured film was baked, and the length, width, and thickness of the film surface were measured, and the dimensional retention of each was calculated. The dimensional retention of the film surface was taken as the average of the dimensional retention in the vertical and horizontal directions. In addition, the thickness of the cured film before and after baking was measured at five points on the film surface, the four corners and the center, and the average value was used. Dimensional retention rate (%, vertical) = vertical length after firing (cm) x 100 / vertical length before firing (cm) Dimensional retention rate (%, width) = Width after firing (cm) x 100 / Width before firing (cm) Dimensional retention rate (%, thickness) = thickness after firing (μm) × 100 / thickness before firing (μm) <Analysis of elemental components in carbon materials> The elemental components present in the carbon material were analyzed by X-ray photoelectron spectroscopy (XPS, ULVAC-PHI, Inc., PHI5000 VersaProbe 2) using AlKα as a monochromatic X-ray light source under the conditions of a voltage of 15 kV and an output of 25 W.
[0097] 〔material〕 The materials used in the production of the benzoxazine compound are shown below.
[0098] (Phenol compounds having aldehyde groups) 4-Hydroxybenzaldehyde (Fujifilm Wako Pure Chemical Industries, Ltd.) (Aromatic diamine compounds) 1,3-bis(4-aminophenoxy)benzene (Seika Corporation) 4,4'-Diaminodiphenyl ether (Seika Co., Ltd.) (Other compounds) Paraformaldehyde (Fujifilm Wako Pure Chemical Industries, Ltd.) [Production Example 1] 1,3-bis(4-aminophenoxy)benzene (20.0000g, 0.0684mol), paraformaldehyde (8.6287g, 0.2873mol), 4-hydroxybenzaldehyde (16.7093g, 0.1368mol), and toluene (105.7887g) were added to a reaction vessel equipped with a stirrer and reacted for 6 hours under reflux. The resulting reaction solution (A) was dried overnight at 60°C under reduced pressure using a vacuum dryer to obtain an aldehyde group-containing benzoxazine compound (a). The molecular weight of the resulting aldehyde group-containing benzoxazine compound (a) was measured by GPC measurement, and the weight average molecular weight (Mw) was 1096 and the number average molecular weight (Mn) was 987. 1 By measuring with H-NMR (heavy solvent: CDCl3), a decrease in the peak of the aldehyde group of 4-hydroxybenzaldehyde at 9.9 ppm and the generation of peaks of benzoxazine rings at 4.6 ppm and 5.4 ppm were observed. From the former, it was confirmed that the raw material was consumed, and from the latter, benzoxazine compound (a) was synthesized.
[0099] As described above, 1,3-bis(4-aminophenoxy)benzene was used as the aromatic diamine compound in Production Example 1. FIG.
[0100] [Production Example 2] 4,4'-Diaminodiphenyl ether (58.4692g, 0.2000mol), paraformaldehyde (25.2302g, 0.8402mol), 4-hydroxybenzaldehyde (48.8505g, 0.4000mol) and toluene (174.0641g) were added to a reaction vessel equipped with a stirrer and reacted for 6 hours under reflux. After cooling the resulting reaction solution (A) to room temperature, the reaction solution (A) was dropped into stirred hexane (600mL) to obtain a viscous precipitate. After removing the supernatant, the resulting precipitate was dried in a vacuum dryer at 110°C under reduced pressure for 15 hours to obtain an aldehyde group-containing benzoxazine compound (b). The molecular weight of the resulting aldehyde group-containing benzoxazine compound (b) was measured by GPC, and the weight average molecular weight (Mw) was 1,168 and the number average molecular weight (Mn) was 927. 1 By measuring by H-NMR (heavy solvent was d6-DMSO), a decrease in the peak of the aldehyde group of 4-hydroxybenzaldehyde at 9.8 ppm and the generation of peaks of benzoxazine rings at 4.7 ppm and 5.5 ppm were observed. It was confirmed from the former that the raw material was consumed and from the latter that benzoxazine compound (b) was synthesized.
[0101] As described above, 4,4'-diaminodiphenyl ether was used as the aromatic diamine compound in Production Example 2. FIG.
[0102] Example 1 The aldehyde group-containing benzoxazine compound (a) obtained in Production Example 1 was placed in a PI film mold (5 cm x 5 cm) having a thickness of 125 μm, and pressed together with a Teflon (registered trademark) sheet (release paper) and a stainless steel plate to obtain a cured film. A MINI TEST PRESS-10 (manufactured by Toyo Seiki Co., Ltd.) was used as the press machine. The processing conditions for obtaining the cured film were as follows. Processing conditions: The resin obtained above was melted at 150°C, then heated to 190°C while applying a pressure of 5 MPa and held for 2 hours, then heated to 220°C and held for 1 hour.
[0103] Example 2 The aldehyde group-containing benzoxazine compound (b) obtained in Production Example 2 was placed in a PI film mold (5 cm x 5 cm) having a thickness of 125 μm, and pressed together with a Teflon (registered trademark) sheet (release paper) and a stainless steel plate to obtain a cured film. A MINI TEST PRESS-10 (manufactured by Toyo Seiki Co., Ltd.) was used as the press machine. The processing conditions for obtaining the cured film were as follows. Processing conditions: The resin obtained above was melted at 150°C, then heated to 190°C while applying a pressure of 5 MPa and held for 2 hours, then heated to 220°C and held for 1 hour.
[0104] Comparative Example 1 Aldehyde group-free benzoxazine resin (product name: Pd) manufactured by Shikoku Kasei was placed in a 125 μm thick PI film mold (5 cm × 5 cm), and molded together with a Teflon (registered trademark) sheet (release paper) and a stainless steel plate by heating and pressing (5 MPa) at 190°C for 2 hours and at 220°C for 1 hour to obtain a cured film. The press machine used was MINI TEST PRESS-10 (manufactured by Toyo Seiki Co., Ltd.).
[0105] Example 3 The aldehyde group-containing benzoxazine compound (a) obtained in Production Example 1 was dissolved in 1,3-dioxolane solvent to prepare a 35 wt% solution. A plain woven material (basis weight: 195 g / m2, 15 cm square) of carbon fiber (Teijin IMS60-6K) was impregnated with the obtained 35 wt% solution to prepare a prepreg. The weight of the solution contained in the prepreg was about 60 wt%, and the weight of the carbon fiber was about 40 wt%.
[0106] Example 4 Four 7.5 cm square pieces were cut out from the prepreg obtained in Example 3 and laminated to obtain a prepreg laminate. Next, together with a Teflon (registered trademark) sheet (release paper) and a stainless steel plate, the prepreg laminate was molded by heating and pressing (5 MPa) at 190°C for 2 hours and at 240°C for 1 hour to obtain a carbon fiber reinforced composite material (fiber composite material). The press used was a MINI TEST PRESS-10 (manufactured by Toyo Seiki Co., Ltd.).
[0107] Example 5 The cured film obtained in Example 1 was placed in a carbonization furnace and baked to obtain a carbon material. The baking was performed using a Denken Co., Ltd. product name: KDF-900GL, heating from 30°C to 1000°C at a temperature increase rate of 5°C / min under a nitrogen flow of 0.5mL / min. The weight retention of the cured film before and after baking was 72%. Furthermore, the in-plane dimensional retention (average of length and width) of the cured film before and after baking was 82%, and the thickness dimensional retention was 87%. The elemental components contained in the obtained carbon material were measured by XPS measurement, and the carbon, oxygen, and nitrogen contents (g) were 94.3% by weight, 3.0% by weight, and 2.7% by weight, respectively, assuming the total content (g) of carbon, oxygen, and nitrogen to be 100% by weight.
[0108] Example 6 The cured film obtained in Example 2 was placed in a carbonization furnace and baked to obtain a carbon material. The baking conditions were the same as those in Example 5. The weight retention of the cured film before and after baking was 72%. Furthermore, the in-plane dimensional retention (average of length and width) of the cured film before and after baking was 82%, and the thickness dimensional retention was 85%. The elemental components contained in the obtained carbon material were measured by XPS measurement, and the carbon, oxygen, and nitrogen contents (g) were 94.0% by weight, 3.0% by weight, and 3.0% by weight, respectively, with the total of the carbon, oxygen, and nitrogen contents (g) being 100% by weight.
[0109] Example 7 The carbon fiber reinforced composite material (fiber composite material) obtained in Example 4 was placed in a carbonization furnace and baked to obtain a carbon material (carbon fiber reinforced carbon composite material). The baking conditions were the same as those in Example 5. The weight retention of the cured film before and after baking was 94%. Furthermore, the in-plane dimensional retention (average of length and width) of the cured film before and after baking was 100%, and the thickness dimensional retention was 96%. The elemental components contained in the obtained carbon material were measured by XPS measurement, and the carbon, oxygen, and nitrogen contents (g) were 97.7% by weight, 1.2% by weight, and 1.1% by weight, respectively, assuming the sum of the carbon, oxygen, and nitrogen contents (g) to be 100% by weight.
[0110] Comparative Example 2: Calcination of Pd-cured film The cured film obtained in Comparative Example 1 was placed in a carbonization furnace and baked to obtain a carbon material. The baking conditions were the same as those in Example 5. The weight retention of the cured film before and after baking was 52%. Furthermore, the in-plane dimensional retention (average of length and width) of the cured film before and after baking was 77%, and the thickness dimensional retention was 66%. The elemental components contained in the obtained carbon material were measured by XPS measurement, and the carbon, oxygen, and nitrogen contents (g) were 93.7% by weight, 3.2% by weight, and 3.1% by weight, respectively, assuming the total content (g) of carbon, oxygen, and nitrogen to be 100% by weight.
[0111] [Evaluation results] The physical properties of each of the Examples and Comparative Examples are shown in the following Tables 1 and 2. Furthermore, the measurement results of the storage modulus in dynamic viscoelasticity for each of the Examples and Comparative Examples are shown in FIG.
[0112] [Table 1]
[0113] [Table 2]
[0114] 4, the cured films of Examples 1 and 2 had higher Tg and Td5 than the cured film of the general-purpose benzoxazine compound of Comparative Example 1. In addition, the cured films of Examples 1 and 2 also had significantly higher residual weight percentages at 800°C than the cured film of Comparative Example 1.
[0115] 3 is a graph showing the storage modulus of Example 1, Example 2, and Comparative Example 1. From FIG. 3, it can be seen that the storage modulus (E') of the cured films of Example 1 and Example 2 is approximately 10 9 Pa. This shows that the cured films of Examples 1 and 2 have a high storage modulus retention performance in the high temperature range. This is thought to be because the cured films obtained by crosslinking the benzoxazine compound having an aldehyde group at the end were able to have a high storage modulus retention performance in the high temperature range.
[0116] Fig. 4 is a graph showing the residual weight ratios of thermogravimetry for Examples 1 and 2 and Comparative Example 1. Fig. 4 shows that the cured films of Examples 1 and 2 maintained high residual weight ratios of roughly 67% or more in the temperature range from 30°C to 1000°C.
[0117] The monomer structure of the aldehyde group-containing benzoxazine compound used in Examples 1 and 2 has an aldehyde group at the end. Therefore, the structure of the cured film crosslinked by opening the benzoxazine ring also contains an aldehyde group, and it is considered that the mobility of the molecule is restricted due to the formation of hydrogen bonds, etc., thereby improving the heat resistance.
[0118] From Table 2, the carbon material of Example 5 (a sample obtained by baking the cured film of Example 1 to 1000°C) and the carbon material of Example 6 (a sample obtained by baking the cured film of Example 2 to 1000°C) both had a weight retention of 72% compared to before baking. This result supports the results of the thermogravimetry in FIG. 4, and the carbon materials of Examples 5 and 6 showed significantly higher weight retention than the carbon material of Comparative Example 2 (a sample obtained by baking the cured film of Comparative Example 1 to 1000°C). In addition, the carbon content of the carbon material was high in all of the carbon materials of Examples 5, 6, 7, and Comparative Example 2. That is, it was confirmed that by using a thermosetting resin according to one embodiment of the present invention, a carbon material having a high weight retention compared to before baking and a high carbon content can be obtained.
[0119] From the above, it can be said that the cured product of the benzoxazine compound containing an aldehyde group exhibits high heat resistance due to the contribution of the aldehyde group in the crosslinked structure. In addition, it can be said that the benzoxazine compound or the carbonized product (carbon material) obtained by baking the cured product of the benzoxazine compound exhibits a high weight retention rate and a high carbon content compared to before baking. Therefore, it is considered that the cured product (cured film) of the thermosetting resin according to one embodiment of the present invention, the carbon fiber reinforced composite material, and the carbonized product (carbon material) thereof can be developed into heat-resistant applications. [Industrial Applicability]
[0120] One aspect of the present invention can be utilized in fields using thermosetting resins.
Claims
1. A thermosetting resin having a benzoxazine ring structure in a main chain, represented by general formula (I), the resin or a cured product of the resin has a carbon content of 85% by weight or more when the resin or a cured product of the resin reaches a maximum temperature of 1000° C. as measured by X-ray photoelectron spectroscopy at a heating rate of 5° C. / min and a nitrogen flow of 0.5 mL / min, where the total content of carbon, nitrogen, and oxygen is taken as 100% by weight; Thermosetting resin. 【Chemistry 1】 [In the general formula (I), Ar 1 and Ar 2 represents a trivalent aromatic group derived from a phenol compound (A) other than vanillin, Ar 1 and Ar 2 may be the same or different, R 1 represents a divalent aromatic group derived from the aromatic diamine compound (B) and represented by any one or more of general formulas (II) to (V). 【Chemistry 2】 [In the general formula (II), The asterisk indicates a bond. The positional relationship of the main chain bonds excluding R which are bonded to the aromatic ring is meta or para; R is a substituent on the aromatic ring and represents an aliphatic group having 1 to 10 carbon atoms, the number of R is 0 or 1 or more, and when the number of R is 2 or more, the Rs may be the same or different, m1 and m2 each represent 0 or 1. 【Chemistry 3】 [In the general formula (III), The asterisk indicates a bond. The positions of the main chain bonds excluding R which are bonded to the two aromatic rings are meta or para, L1 represents one or more of a single bond, an isopropylidene group, a sulfonyl group, a carbonyl group, a 9,9-fluorenyl group, an oxy group, and an alkylene group; R is a substituent on an aromatic ring and represents an aliphatic group having 1 to 10 carbon atoms, the number of R in each aromatic ring is 0 or 1 or more, and when the number of R is 2 or more, they may be the same or different, m3 and m4 each represent 0 or 1. 【Chemistry 4】 [In the general formula (IV), The asterisk indicates a bond. The positions of the main chain bonds excluding R which are bonded to the three aromatic rings are meta or para, L2 and L3 each represent an oxy group; R is a substituent on an aromatic ring and represents an aliphatic group having 1 to 10 carbon atoms, the number of R in each aromatic ring is 0 or 1 or more, and when the number of R is 2 or more, they may be the same or different, m5 and m6 each represent 0 or 1. 【Chemistry 5】 [In the general formula (V), The asterisk indicates a bond. The positions of the main chain bonds excluding R which are bonded to the four aromatic rings are meta or para, L4 and L6 each represent an oxy group; L5 represents one or more of a single bond, an isopropylidene group, a sulfonyl group, a carbonyl group, and a 9,9-fluorenyl group; R is a substituent on an aromatic ring and represents an aliphatic group having 1 to 10 carbon atoms, the number of R in each aromatic ring is 0 or 1 or more, and when the number of R is 2 or more, they may be the same or different, m7 and m8 each represent 0 or 1.
2. The aromatic diamine compound (B) is at least one selected from the group consisting of 4,4'-oxydianiline, 1,4-diaminobenzene, 1,3-diaminobenzene, 2,4-diaminotoluene, 2,6-diaminotoluene, 3-(aminomethyl)benzylamine, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, bis[4-(4-aminophenoxy)phenyl]sulfone, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, and 9,9-bis(4-aminophenyl)fluorene, according to claim 1.
3. A composition comprising the thermosetting resin of claim 1.
4. An uncured molded article obtained by molding the composition according to claim 3.
5. A cured molded article obtained by curing the composition according to claim 3.
6. A prepreg or semipreg obtained by impregnating reinforcing fibers with the composition according to claim 3.
7. A carbon material obtained by carbonizing and / or graphitizing the uncured molded article according to claim 4 or the cured molded article according to claim 5.
8. A carbon material obtained by impregnating reinforcing fibers with the composition according to claim 3, curing the resulting fiber composite material, and then carbonizing and / or graphitizing the resulting fiber composite material.
9. A carbon material obtained by carbonizing and / or graphitizing the prepreg or semipreg according to claim 6.
Citation Information
Patent Citations
Curable resin composition, film, prepreg, and cured product
JP2014148562A
Thermosetting resin composition, prepreg, fiber-reinforced composite material, and method for producing the same
JP2018062540A